Play Mode Effect of Exergames on Subthreshold Depression Older Adults: A Randomized Pilot Trial - Li, Jinhui; Theng, Yin-Leng; Foo, Schubert (Frontiers in Psychology, 2020)
Background: Subthreshold depression is a common mental disorder in late life. Increasing studies have supported the positive effects of exergames to subthreshold depression. The current study aims to investigate how play mode potentially affects exergames’ effects on subthreshold depression among older adults. Method: A between-group experiment was carried out to compare the effect of exergames with different play modes. Fifty-two Singaporean older adults with subthreshold depression were randomly assigned into two conditions, and performed either single-player or multiple-player Nintendo Wii Tennis exergames for 6 weeks, while the key variables of depression, social support and loneliness were measured at both pre- and post-study period. Results: Findings from path analysis suggested that older adults in multiple-player exergames experienced lower levels of loneliness, and further more reduction on subthreshold depression, when compared to those in single-player exergames. Although social support was not affected by play mode, the significant relationship among social support, loneliness, and depression was found in the context of exergaming. Conclusion: This study not only provides additional insight into a possible causal association lining play mode and health outcomes of exergames, but also opens the discussion of how to optimise antidepressive effect of exergames for older adults.